A silicon‐labelled amino acid suitable for late‐stage fluorination and unexpected oxidative cleavage reactions in the preparation of a key intermediate in the Strecker synthesis. Issue 3 (20th April 2018) - Scroggie, Kymberley R.; Alcock, Lisa J.; Matos, Maria J.; Bernardes, Gonçalo J. L.; Perkins, Michael V.; Chalker, Justin M.
Abstract: A novel silicon‐substituted phenylalanine derivative was prepared using the Strecker amino acid synthesis. An unexpected oxidative cleavage was observed in the preparation of the aldehyde required for the Strecker reaction. In this step, a homobenzylic alcohol intermediate was oxidatively cleaved to the corresponding benzaldehyde using either chromium or palladium based oxidants. This undesired side reaction was overcome through the use of Dess‐Martin Periodinane, or through an efficient TEMPO‐bleach oxidation. The amino acid prepared in this study was then labelled with fluoride in aqueous solvent using a range of fluoride sources. The efficiency of this labelling motivates future studies in late‐stage fluorination of peptide and protein therapeutics for use in positron emission tomography. Abstract :